The Development of Network Society Theory - O K Trubitsyn (RUDN Journal of Philosophy, 2011)
The article offers a systematic analysis of the issues related to the network society as a subject matter of theoretical research. The organizational structures classification is provided primarily to expose the peculiar features of hierarchical and network structures. The origins and sources of network management philosophy are pointed out and the reasons for its growing popularity are examined. Further on the author focuses on the shaping of the network society concept per se offering insight into its three most popular modifications, i.e., the soft (moderate) modernist perspective, the soft postmodernist, and the hard (radical) postmodernist one. Finally, the key discussion points in the wake of network society development in the Russian conservative patriotic circles are outlined to demonstrate social significance of the topic involved.